“Fold the Eggs … Fold the Eggs … ”: Experiences of Educational Stakeholders During COVID-19 - Bharaj, Pavneet Kaur; Singh, Anisha (Frontiers in Education, 2021)
As the world experienced the COVID-19 outbreak, education was one of the multiple systems that were hit hard. We explored the consequences of the reconfiguration of schooling based on the experiences of the educational stakeholders caught up in the sudden transition to virtual schooling during COVID-19. Using Bronfenbrenner’s (1976) Ecological Systems framework, we underscored the complexity of the individual’s socio-cultural world and the myriad influences that impact the individual’s growth to examine how agents involved in the educational system have dealt with this unanticipated crisis academically, personally, socially, and emotionally. Recognizing that multiplicity of voices might bring a different perspective, we captured various voices – an administrator leading the teachers’ professional development, a public-school elementary teacher, and a parent with two kids. Using unstructured interviews, we unpacked the narratives and counter-narratives of the participants to unpack ‘what worked’ and ‘what did not work’ during virtual learning and teaching environment. The voices centered in this article offer a rich source of insight into challenges faced by those who are at the forefront of the educational crisis – teachers and parents. The results showed how various communities cooperated to deal with such unprecedented times while maintaining the responsibility of educating children. The key trends that emerged from our qualitative investigation were: (a) development of collaboration among teachers as they transitioned into virtual teaching, (b) flexibility of the school leaders to assist the teachers in this new instructional modality, and (c) parents’ acknowledgment of the teachers’ efforts to assist their children.